Acceptor engineering of quinone-based cycloparaphenylenes via post-synthesis for achieving white-light emission in single-molecule - Xiaonan Li; Lin Liu; Luyang Jia; Zhe Lian; Jing He; Shengzhu Guo; Ying Wang; Xuebo Chen; Hua Jiang (Nature Communications)
Abstract Developing donor-acceptor [n]cycloparaphenylenes (D-A [n]CPPs) with multiple emissions from different emissive states remains challenging yet crucial for achieving white-light emission in single-molecule. Here, we report our explorations into acceptor engineering of quinone-based D-A [10]CPPs (Nq/Aq/Tq[10]CPPs) via a post-lateral annulation using Diels-Alder reactions of oxTh[10]CPP. X-ray analysis reveals that Nq[10]CPP displays a side by side packing via naphthoquione stacking while Aq[10]CPP adopts an intercalated conformation through anthraquinone interaction. Fluorescence investigations reveal that the quinone-based [10]CPPs display distinctive acceptor-dependent dual-emission from both the locally excited state and charge transfer state after single-wavelength excitation in organic solvents, consequently leading to multicolor emissions, in particular, white-light emission in CHCl3 for Aq[10]CPP. In THF/water mixture, quinone-based [10]CPPs and oxTh[10]CPP display a wide range of fluorescence emissions including white-light emission as increasing the fraction of water, accompanying by the formation of nanoparticles as demonstrated by Tyndall effect and SEM. Interestingly, the fluorescence of Aq[10]CPP can be switched from white to blue in CHCl3 upon redox. Our investigations demonstrate that acceptor engineering not only endows quinone-based [10]CPPs with two distint emissive states for achieving white-light emission but also highlights an effective post-synthetic strategy for functionalizing CPP nanohoops with desirable properties.